Audit Quality Model Moderated by Professional Skepticism: Determinants of Professional Ethics and Auditor Experience - LANNAI, Darwis; HAJERING, Hajering; AHMAD, Hamzah (Theoretical and Practical Research in Economic Fields, 2025)
This research explores how an auditor’s experience and professional ethics influence audit quality, with professional skepticism playing a key moderating role. Experience sharpens an auditor’s ability to detect fraud, while strong ethics help them uphold integrity. Together, these factors shape professional skepticism - the cautious, questioning mindset auditors use when reviewing evidence and making decisions. The study was carried out by the South Sulawesi Provincial Audit Board in early 2024, focusing on auditors in Makassar. Rather than selecting a sample, the researchers included all 35 auditors in the city, ensuring comprehensive insights. Using field research methods, the analysis revealed that both experience and ethics significantly improve audit quality. Additionally, professional skepticism was found to positively mediate this relationship, reinforcing how critical a questioning attitude is in high-quality audits. By highlighting these connections, the study contributes to building a clearer model for how experience, ethics, and skepticism work together to enhance audit outcomes.